If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(8 + -5a) + -1(14 + 4a) + -19 = -1(8 + -7a) + (-1a) + 7 (8 * -1 + -5a * -1) + -1(14 + 4a) + -19 = -1(8 + -7a) + (-1a) + 7 (-8 + 5a) + -1(14 + 4a) + -19 = -1(8 + -7a) + (-1a) + 7 -8 + 5a + (14 * -1 + 4a * -1) + -19 = -1(8 + -7a) + (-1a) + 7 -8 + 5a + (-14 + -4a) + -19 = -1(8 + -7a) + (-1a) + 7 Reorder the terms: -8 + -14 + -19 + 5a + -4a = -1(8 + -7a) + (-1a) + 7 Combine like terms: -8 + -14 = -22 -22 + -19 + 5a + -4a = -1(8 + -7a) + (-1a) + 7 Combine like terms: -22 + -19 = -41 -41 + 5a + -4a = -1(8 + -7a) + (-1a) + 7 Combine like terms: 5a + -4a = 1a -41 + 1a = -1(8 + -7a) + (-1a) + 7 -41 + 1a = (8 * -1 + -7a * -1) + (-1a) + 7 -41 + 1a = (-8 + 7a) + (-1a) + 7 Reorder the terms: -41 + 1a = -8 + 7 + 7a + (-1a) Combine like terms: -8 + 7 = -1 -41 + 1a = -1 + 7a + (-1a) Combine like terms: 7a + (-1a) = 6a -41 + 1a = -1 + 6a Solving -41 + 1a = -1 + 6a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-6a' to each side of the equation. -41 + 1a + -6a = -1 + 6a + -6a Combine like terms: 1a + -6a = -5a -41 + -5a = -1 + 6a + -6a Combine like terms: 6a + -6a = 0 -41 + -5a = -1 + 0 -41 + -5a = -1 Add '41' to each side of the equation. -41 + 41 + -5a = -1 + 41 Combine like terms: -41 + 41 = 0 0 + -5a = -1 + 41 -5a = -1 + 41 Combine like terms: -1 + 41 = 40 -5a = 40 Divide each side by '-5'. a = -8 Simplifying a = -8
| s=lw+wh+lh | | 2a^2(3a^3-5a^2)= | | 56x^2-19x=15 | | 4.5x+1.10x=36.10 | | 2h=w-3p | | 9-3x=x-14 | | 6[z-(10z+86)+5]=2(z+9) | | 5c-17-2x=6x-1-x | | Ir=v | | 2p-2(4-3p)=3(p-2)-37 | | p^2+4p+16=0 | | 11+w=-27 | | -9(x+4)+2x+7=6x+8 | | 6(3x-4)=5-(x+2) | | 5r^2-7r-6= | | -8-p=15 | | 6-2x=5x-9x+14-8 | | 44+3x+20x=180 | | 44+3x+29x=180 | | 5x^2+15xy+4rx+12r= | | 9x=117 | | -5(x+4)+7=8-(x-9) | | -4.6z+2.2z=4.8 | | f^2+12f+32=0 | | d^2-7d+4=0 | | 9x-4(5-2x)=-(3-x) | | 4p+5-7p=-7 | | 5w-4=21 | | y^2=8 | | 2n-(6n+5)=9-(2n-1) | | n^2-4n-3=0 | | 2n-(6n+5)=9-(2n+1) |